2012
DOI: 10.1021/jp304003c
|View full text |Cite
|
Sign up to set email alerts
|

Reentrant Nematic Phenomenon in a New Class of Low Molar Mass, Single-Component Liquid Crystals

Abstract: We report the observation of reentrant nematic behavior in a relatively new class of compounds, namely, dimerlike mesogens that are made by covalently linking nematogenic cyanobiphenyl and nonmesogenic N-(n-alkyl)salicylaldimine segments through a central flexible spacer of varying length and parity. The existence of reentrant phenomenon in this class of mesogens, evidenced indubitably by means of several complementary studies, appears to be crucially dependent on the length of the terminal alkyl tail and pari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 63 publications
3
10
0
Order By: Relevance
“…The qualitative miscibility study further supported the N−SmA−N re sequence with the nematic phase exhibiting re-entrance. 81 An optical transmission profile obtained clearly supports the phase transitions deduced from both calorimetric and optical studies. 74 To reveal the molecular arrangement, the SmA phase occurring between two nematic phases was probed with the help of an XRD technique.…”
Section: Articlesupporting
confidence: 69%
“…The qualitative miscibility study further supported the N−SmA−N re sequence with the nematic phase exhibiting re-entrance. 81 An optical transmission profile obtained clearly supports the phase transitions deduced from both calorimetric and optical studies. 74 To reveal the molecular arrangement, the SmA phase occurring between two nematic phases was probed with the help of an XRD technique.…”
Section: Articlesupporting
confidence: 69%
“…Scheme shows the synthetic steps followed to prepare the eight pairs of enantiomers. To begin with, 4′‐hydroxy‐4‐cyanobiphenyl was alkylated with α,ω‐dibromoalkanes in the presence of anhydrous K 2 CO 3 in butanone to obtain 4′‐((ω‐bromoalkyl)oxy)‐4‐cyanobiphenyls ( 1 a – h ) in good yields . The reaction of 2,4‐dihydroxybenzaldehyde with cyanobiphenyls ( 1 a – h) in the presence of a mild base in butanone yielded the respective O ‐alkylated products, namely, 4′‐((ω‐(4‐formyl‐3‐hydroxyphenoxy)alkyl)oxy)‐4‐cyanobiphenyls ( 2 a – h ) .…”
Section: Resultsmentioning
confidence: 99%
“…Powder XRD studies have shown that the SmA phase formed by polar mesogens (i.e., with a terminal cyano group) generally consist of antiparallel pairs . The pairing of polar mesogens results from the strong intermolecular longitudinal association so as to minimize the dipolar energy contribution effectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations